2020
DOI: 10.1101/2020.07.14.20153353
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Circulating argonaute-bound microRNA-126 reports vascular dysfunction & response to treatment in acute & chronic kidney disease

Abstract: Background: Vascular and kidney dysfunction commonly co-exist. There is an unmet need for biomarkers of vascular health. Circulating microRNAs (miRs) are disease biomarkers; miR-126 is endothelial cell-enriched. We measured circulating miR-126 in rats with nephrotoxic nephritis (NTN) and humans with acute endothelial and renal injury (vasculitis associated with autoantibodies to neutrophil cytoplasm antigens (ANCA)). We then compared these findings to those from patients with chronic kidney disease (CKD) and e… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 50 publications
(61 reference statements)
0
1
0
Order By: Relevance
“…Moreover, miRNAs participate in cellular process, including the growth of renal tubular epithelial cells (13,14). Meanwhile, miRNAs have been reported to be associated with AKI progression (15)(16)(17). For instance, miR-21 has been shown to inhibit the progression of AKI (18); Jiang et al (19) found that miR-500a-3p alleviated kidney injury by targeting mixed lineage kinase domain like pseudokinase.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, miRNAs participate in cellular process, including the growth of renal tubular epithelial cells (13,14). Meanwhile, miRNAs have been reported to be associated with AKI progression (15)(16)(17). For instance, miR-21 has been shown to inhibit the progression of AKI (18); Jiang et al (19) found that miR-500a-3p alleviated kidney injury by targeting mixed lineage kinase domain like pseudokinase.…”
Section: Introductionmentioning
confidence: 99%